2020
DOI: 10.1016/j.psychres.2020.112840
|View full text |Cite
|
Sign up to set email alerts
|

Designing a feasible exercise intervention in first-episode psychosis: Exercise quality, engagement and effect

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…This study was commenced following approval from the NIHR HRA ethics committee (West Midlands-Edgbaston REC 17/WM/0412). Intervention design, quality and patient-oriented outcomes were assessed and are summarised by Fisher et al 45 .…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was commenced following approval from the NIHR HRA ethics committee (West Midlands-Edgbaston REC 17/WM/0412). Intervention design, quality and patient-oriented outcomes were assessed and are summarised by Fisher et al 45 .…”
Section: Participantsmentioning
confidence: 99%
“…Participants in the exercise group reported a 10.98% decrease in PANSS general score, compared to a 2.82% decrease observed in participants in the control group (SMD = −0.24). These data have been assessed alongside other functional measures that better shape the psychotic state, and the effects of the exercise intervention in Fisher et al 45 .…”
Section: Retention Exercise Quality and Psychopathologymentioning
confidence: 99%
“…For this reason, early psychosis could be the optimal phase for introducing exercise to prevent or mitigate comorbid metabolic abnormalities and physical disorders [ 14 ]. However, to our knowledge, only few previous studies [ 19 23 ] have explored exercise as the primary/dominant intervention module in early psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Fisher et al recently published the results of a randomised feasibility study investigating exercise quality, engagement and effect of a 12-week intervention involving exercise training (40–60 min 2–3 times a week) in 22 male mental health service users with psychosis (24.8 ± 4.8 years) [ 22 , 23 ]. While the authors did not observe significant changes in weight or body mass index in either group, the study demonstrated that engaging first-episode psychosis patients in exercise was possible [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation